2022
DOI: 10.3390/ijms23147983
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Biomarkers of the Apnea Hypopnea Index and Obstructive Sleep Apnea: Insights into the Pathophysiology of Presence, Severity, and Treatment Response

Abstract: Obstructive sleep apnea (OSA), a disease associated with excessive sleepiness and increased cardiovascular risk, affects an estimated 1 billion people worldwide. The present study examined proteomic biomarkers indicative of presence, severity, and treatment response in OSA. Participants (n = 1391) of the Stanford Technology Analytics and Genomics in Sleep study had blood collected and completed an overnight polysomnography for scoring the apnea–hypopnea index (AHI). A highly multiplexed aptamer-based array (So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…E-selectin, a cellular adhesion molecule [ 37 ], was upregulated in the shortest sleep quintile which is supported by at least one study in which one night of sleep deprivation was associated with increased concentrations of soluble E-selectin [ 38 ]. Moreover, E-selectin concentrations are increased in obstructive sleep apnea [ 39 ] and are reduced following treatment with continuous positive airway pressure [ 39 , 40 ]. Those findings suggest that concentrations of E-selectin may rapidly adjust with changes to sleep dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…E-selectin, a cellular adhesion molecule [ 37 ], was upregulated in the shortest sleep quintile which is supported by at least one study in which one night of sleep deprivation was associated with increased concentrations of soluble E-selectin [ 38 ]. Moreover, E-selectin concentrations are increased in obstructive sleep apnea [ 39 ] and are reduced following treatment with continuous positive airway pressure [ 39 , 40 ]. Those findings suggest that concentrations of E-selectin may rapidly adjust with changes to sleep dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that eight proteins (tissue type plasminogen activator, amyloid-like protein 1, plasminogen activator inhibitor 1, secretogranin 3, cystine-rich protein 1, prosurvival protein 1, sex hormone binding globulin, and desmoglein 2) likely predicted the presence and severity of obstructive sleep apnoea; and five protein Azarbarzin 2019, 45 Trzepizur 2022, 21 Blanchard 2021, 48 markers (C reactive protein, tissue type plasminogen activator, plasminogen activator inhibitor 1, tartrate resistant acid phosphatase type 5, and soluble E-selectin) were significantly affected by continuous positive airway pressure or positive airway pressure (P=0.004, P=0.047, P=0.007, P=0.009, P=0.030, respectively). 72 These results suggested that the subset of proteins might be promising markers in the management of obstructive sleep apnoea. Markers of inflammation might also help group patients with obstructive sleep apnoea.…”
Section: Advanced Polysomnographic Metricsmentioning
confidence: 94%
“…71 In a recent study, multivariate protein measurement was used to quantify 5000 proteins cross sectionally in the plasma of 1391 clinic patients in relation to the presence and severity of obstructive sleep apnoea. 72 The effect of treatment with continuous positive airway pressure or positive airway pressure on the proteins identified was also examined to explore potential pathophysiological mechanisms in two separate intervention based cohorts with obstructive sleep apnoea. The study showed that eight proteins (tissue type plasminogen activator, amyloid-like protein 1, plasminogen activator inhibitor 1, secretogranin 3, cystine-rich protein 1, prosurvival protein 1, sex hormone binding globulin, and desmoglein 2) likely predicted the presence and severity of obstructive sleep apnoea; and five protein Azarbarzin 2019, 45 Trzepizur 2022, 21 Blanchard 2021, 48 markers (C reactive protein, tissue type plasminogen activator, plasminogen activator inhibitor 1, tartrate resistant acid phosphatase type 5, and soluble E-selectin) were significantly affected by continuous positive airway pressure or positive airway pressure (P=0.004, P=0.047, P=0.007, P=0.009, P=0.030, respectively).…”
Section: Advanced Polysomnographic Metricsmentioning
confidence: 99%
“…The GPL6244 (Affymetrix Human Gene 1.0 ST Array) platform was used for both GSE135917 and GSE38792 datasets. Studies have shown that continuous positive airway pressure (CPAP) can alter the expression profiles of OSA patients [ 36 , 37 , 38 ], even returning them to their initial, untreated levels [ 39 ]. We were therefore concerned that including the transcriptome of patients undergoing CPAP treatment may have masked changes that were strongly linked to the occurrence and development of OSA.…”
Section: Methodsmentioning
confidence: 99%